Identification of High‐Occupancy Areas and Movement Dynamics of Age‐0 Lake Sturgeon in the Lower Fox River, Wisconsin. Issue 6 (14th October 2022) - Tucker, Stefan; Houghton, Christopher J.; Harris, Brandon; Elliott, Robert; Donofrio, Michael; Forsythe, Patrick S.
Abstract: The lower Fox River (LFR) is a highly urbanized and fragmented system with a legacy of pollution. Benthic dredging and sediment cleanup combined with capping have been implemented with the goal of remediating the polychlorinated biphenyl contamination and improving the health of resident fish and wildlife populations. The LFR hosts a small population of adult Lake Sturgeon Acipenser fulvescens that spawns at the base of the first barrier, De Pere Dam. Recent research suggests that larval production is limited and no juveniles have been documented residing within the system, although limited sampling has been conducted. The objectives of this study were to describe age‐0 Lake Sturgeon movement patterns, quantify the duration of river residency, and identify areas of congregation in the LFR. To track fish, a total of 38 age‐0 and 1 age‐1 Lake Sturgeon were obtained from nearby wild populations and hatchery settings, implanted with acoustic transmitters, released below De Pere Dam, and actively tracked, daily, for ~40 d (August–October in 2018 and 2019). Sixty‐nine percent of the acoustically tracked age‐0 Lake Sturgeon remained in the LFR for >50% of the study period, and emigration events appear to be related to increases in river discharge. Individuals residing within the LFR tend to congregate within six areas of the LFR encompassing 6% of total river area. The results suggest that suitable habitat exists in the LFR for age‐0 and age‐1 Lake Sturgeon, that discharge may cue downstream movement, and that high‐occupancy areas (likely areas of preferred habitat) are present in the LFR. Long‐term monitoring of larval production, survival, and age‐0/juvenile dynamics will continue to help identify recruitment bottlenecks, improve knowledge of juvenile ecology, and guide future restoration goals.